CLL: novel prognostics, and updates on therapy 1 - Brown, Jennifer R. (Henry Stewart Talks, 2015)
Somatic genetics of CLL, Novel prognostics, Predictive markers, Frontline therapy, Clinical trials (study design and outcomes)